TRADISI PAWANG PADA MASYARAKAT DESA REMBAN MURATARA SUMATERA SELATAN - Wira Hadikusuma; Rozian Karnedi; Japarudin Japarudin (Manthiq, 2023)
Abstract: This research is motivated by the phenomenon of the rain handler tradition in Remban Village, Rawas Ulu, North Musi Rawas. This traditional ritual has a strong mystical smell even though it is in a modern and sophisticated era, and there is still a lack of people who understand the meaning of this tradition. This study aims to analyze the chramer tradition philosophically. As for the formulation of the problem; 1) Why do the people of Remban Village still carry out the chramer tradition. 2) What is the philosophical meaning of the chramer tradition. This research is a type of field research that uses descriptive qualitative research methods with a philosophical approach. The results are as follows; First, the Remban Village Community continues to carry out the Charmer tradition, the reasons are; The tradition has been passed down from generation to generation, the need for the smooth running of the event, the requirements are easy, the costs for traditional events are very small, the majority did not rain when the rain conditions were installed. Second, the philosophical meaning of the objects used in the chramer tradition; Red agarwood as a medium of communication with the supernatural. Seven kinds of flowers signify fragrance, fertility, pleasure. Green coconut means concern for others for those in need. The four Janurs represent the symbols of the four companions of the Prophet Muhammad. Roses mean the smooth running of the event. Kantil flowers indicate that the event is as expected. The ylang flower asks to be subject to what we put as a condition, so that it doesn't rain. Water means fertility.Keywords: Charmer Tradition, Remban Village, PhilosophicalÂ Â Abstrak: Penelitian ini dilatarbelakangi fenomena tradisi pawang hujan di Desa Remban Kecamatan Rawas Ulu Kabupaten Musi Rawas Utara. Ritual tradisi tersebut sangat kental berbau mistis walaupun berada di era modern dan canggih, serta masih kurangnya masyarakat yang memahami makna dari tradisi tersebut. Penelitian ini bertujuan untuk menganalisis tradisi Pawang secara filosofis. Adapun rumusan masalahnya; 1) Mengapa masyarakat Desa Remban masih menjalankan tradisi Pawang. 2) Apa makna filosofis dari tradisi Pawang. Penelitian ini merupakan jenis penelitian lapangan yang menggunakan metode penelitian deskriptif kualitatif dengan pendekatan filosofis. Adapun hasilnya sebagai berikut; Pertama, Masyarakat Desa Remban tetap melakukan tradisi Pawang alasannya adalah; Tradisi turun temurun, kebutuhan dalam kelancaran acara, syarat yang mudah, biaya acara tradisi yang sangat sedikit, mayoritas tidak terjadi hujan ketika dipasang syarat hujan. Kedua, Makna simbol dari perbendaan yang digunakan dalam tradisi Pawang; Gaharu merah sebagai media komunikasi dengan alam ghaib. Bunga tujuh rupa menandakan keharuman, kesuburan, kesenangan. Kelapa hijau bermakna kepedulian dengan sesama bagi yang membutuhkan. Janur empat buah mewakili simbol dari empat sahabat Rosulullah. Bunga mawar bermaksud kelancara acara. Bunga kantil mengisyaratkan semoga acara sesuai dengan yang diharapkan. Bunga kenanga meminta supaya kena apa yang kita pasang sebagai syarat, supaya tidak terjadi hujan. Air bermakna kesuburan.Kata Kunci: Tradisi Pawang, Desa Remban, Filosofis.